Clinical outcome of cycles with oocyte degeneration after intracytoplasmic sperm injection. (4th March 2017) - Liu, Lanlan; Cai, Jiali; Li, Ping; Jiang, Xiaoming; Ren, Jianzhi
ABSTRACT: There are variant rates of oocyte degeneration after intracytoplasmic sperm injection (ICSI) among different patients. Oocyte degeneration after ICSI may reflect the cohort of oocyte quality and subsequent embryo development capacity and clinical outcome. This retrospective study analyzed 255 cycles with at least one degenerated oocyte after ICSI (degeneration group) and 243 cycles with no degenerated oocytes after ICSI (control group). Basic characteristics like female age, body mass index, duration of infertility, hormone (FSH, LH, E2 ) levels on day 3 of menses, and primary infertility patient rate were similar between the two groups ( p > 0.05). Total dose of gonadotropin and length of stimulation were also similar between the two groups ( p > 0.05), but the degeneration group exhibited a more exuberant response to ovarian stimulation as reflected by more oocytes retrieved ( p < 0.05). The number of 2PN embryos available and high quality embryos were similar between the two groups ( p > 0.05), but the high quality embryo rate, early cleavage embryo rate, and available embryo rate were all statistically lower than the control group ( p < 0.05). Embryo developmental kinetics seemed to be disturbed and embryo fragmentation rate increased in the degeneration group ( p < 0.05). However, there was no statistical difference in the distribution of graded embryos transferred, and there were no statistical differences in the pregnancy rate, implantation rate, and abortion rate between the two groups ( p > 0.05). We deduce that the presence of oocyte degeneration after ICSI may be associated with decreased embryo quality with embryo development kinetics disturbed. However, the clinical outcomes may not be affected if the premise that sufficient high quality degeneration group embryos are available for transfer.